Reading Dysfunction and Dyslexia, Effectiveness of Convergence, Accommodative Facility, and Saccades: A Systematic Review - Hanieh Falahati; Amanullah Soltani; Mitra Kamyabi; Hamdaleh Manzari-Tavakoli (Vesnu Publications, 2020)
Introduction: Dyslexia is a combination of problems that affect the learning process in one or more areas, including reading, writing, and spelling and may be associated with problems with processing speed, memory, visual-auditory perception, motor skills, and  speech. Skills like comprehension and distinction of letters and sounds, communication between phonograph and writing, naming and representing letters, memory, movements, and visual and cognitive factors are concomitantly involved in this complex cognitive process. The aim of this study is to review the research available on the effectiveness of convergence, accommodative facility, and saccades on reading failure.Materials and Methods: The articles concerning dyslexia, reading disorder, phonological processing, effectiveness of convergence, saccade, and accommodative facility published between 2010 and 2020 at Google Scholar, Pubmed, and ScienceDirect databases, as well as in Persian dissertations and journals indexed in Scientific Information Database (SID) and Magiran. "Reading disorder, Dyslexia, Convergence, Accommodative facility, Saccade, Visual function, Visual perception, Visual processing, Adaptive effectiveness, Phonology recognition", and their combinations according to Medical Subject Headings (MeSH) were used as the main keywords. The results of 18 articles were analyzed in the present study.Results: There was a significant relationship between the disorder of accommodative facility and eye movements, saccade, and dyslexdia, in a way that improving visual interventions, visual and motor perception skills, rehabilitation of basic visual functions, and saccades enhanced the accommodative facility of visual functions and reading function of students. In other words, to prevent problems or poor performance of children and students with dyslexia, more attention should be paid to these skills.Conclusion: It seems that processing of the vision perception plays an important role in reading impairment, and people who have received convergence exercises, accommodative facility, and saccade movements, including training in visual-motor perception skills, perform better in reading.